The role of tourism in shaping of conditions and quality of life of the inhabitants of a small town. Case study of Hel (Poland) - Kulawiak, Anita; Smętkiewicz, Karolina (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2021)
The development of the tourism function, in the light of the current literature on the subject, can have a twofold effect on the locality in which the function develops. Most often it is a source of many positive changes which can be observed both in the social and economic sphere, but there is also evidence that excessive concentration of tourism brings about negative effects, e.g. excessive commercialisation and degradation of attractive and unique spaces. In the context of the disproportions observed, this paper aims to determine the relationship between the development of the tourism function and selected elements of the living conditions and quality of life of the inhabitants of Hel, one of the most popular cities in Poland. The primary source of data was a questionnaire interview conducted on a group of 327 town residents (10% of the total population) in May and July 2018. The aim of the research was, on the one hand, to identify the residents’ opinions on the conditions and quality of life in Hel and, on the other hand, to try to answer the question whether the tourist function primarily influences the population’s economic activation, physiognomy and general attractiveness of the town. The results obtained showed that in the case of Hel tourism has a positive impact on most of the above mentioned features and in the eyes of the inhabitants it is a source of many beneficial changes for the town.